Residential property valuation using GIS - Bohari, Sharifah Norashikin (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1998)
Valuation of properties especially residential properties commonly done manually or based on current report and site investigation and mostly it was recorded in a paper form and hardcopies. The current trend to revaluation properties is developing a property valuation model which also capable to estimate residential properties values in a large scale and short period. Geographic Information System (GIS) also provide capable tools that can be used to record all information about value of properties and can be displayed as spatial based information. This study demonstrates the development of property valuation model using the Ordinary Least Square (OSL) method to estimate residential properties values for state of Perlis, Malaysia. The model was developing in ArcGIS software. The effectiveness of the OLS would be examined by referring to the accuracy of the model and the significant of the model's variables, conducted through a series of model tests and compared the models predicted value with the present value.